Huge abdominal swelling due to haemorrhagic splenic cyst (Bangladesh Medical Journal Khulna, 2017)
Splenic cyst is an uncommon problem in surgical practice. It is usually diagnosed in scanning procedure. In some cases it produces symptoms like abdominal mass, abdominal pain, distention, constipation either due to haemorrhage, rupture or big size. In our case, patient presents with abdominal pain, distention, vomiting, constipation and respiratory embarrassment. Routine investigation was done and diagnosis was confirmed after laparotomy, Splenectomy was done. Post operative recovery was good.Bang Med J (Khulna) 2016; 49 : 34-36